2009
DOI: 10.1212/wnl.0b013e3181a82621
|View full text |Cite
|
Sign up to set email alerts
|

A case of NMO seropositive for aquaporin-4 antibody more than 10 years before onset

Abstract: Neuromyelitis optica (NMO) is characterized by severe optic neuritis and longitudinally extended transverse myelitis (LETM). The clinical and laboratory features of NMO are different from multiple sclerosis (MS). 1 An autoantibody to aquaporin-4 (AQP4) has been detected exclusively in the NMO sera. 1 Moreover, we demonstrated an extensive loss of AQP4 and glial fibrillary acidic protein immunoreactivities in the perivascular regions with complement and immunoglobulin deposition in NMO that suggests astrocytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(93 citation statements)
references
References 7 publications
5
86
0
2
Order By: Relevance
“…This finding may be explained by subclinical levels of circulating AQP4-IgG, which may be present years before clinical presentation. 24,25 The miscarriage rate of 42.9% is outside the 95% CI that would be expected if the true miscarriage rate post-NMOSD was equal to reported rates in multiple sclerosis (expected 95% CI 1.29%-40.9%) 26,27 and just within the expected range calculated from published rates in systemic lupus erythematosus (expected 95% CI 2.56%-45.5%). 28 This suggests that the miscarriage rate in patients with NMOSD is higher than in patients with multiple sclerosis, although larger prospective studies with adequate control groups are needed to test this hypothesis.…”
mentioning
confidence: 55%
“…This finding may be explained by subclinical levels of circulating AQP4-IgG, which may be present years before clinical presentation. 24,25 The miscarriage rate of 42.9% is outside the 95% CI that would be expected if the true miscarriage rate post-NMOSD was equal to reported rates in multiple sclerosis (expected 95% CI 1.29%-40.9%) 26,27 and just within the expected range calculated from published rates in systemic lupus erythematosus (expected 95% CI 2.56%-45.5%). 28 This suggests that the miscarriage rate in patients with NMOSD is higher than in patients with multiple sclerosis, although larger prospective studies with adequate control groups are needed to test this hypothesis.…”
mentioning
confidence: 55%
“…A depletion of antibodies below a detectable threshold could explain a negative serostatus. Although, anti-AQP4 antibodies have been detected up to ten years before disease onset (Nishiyama et al, 2009), we have analyzed a small number of patients who were initially negative for NMO IgG and turned out to be low titer positive in longitudinal samples (unpublished results). For this reasons, one has to be careful when dealing with the term "seronegative NMO".…”
Section: "Anti-aqp4 Seronegative Nmo"mentioning
confidence: 99%
“…Latest findings by Pohl et al showed that AQP4 specific T cells are capable of inducing brain inflammation mainly in astrocytic glia limitans and therefore enable an entry of anti-AQP4 autoantibodies (Pohl et al, 2011). As anti-AQP4 antibodies are detectable more than ten years before disease onset (Nishiyama et al, 2009), the time point when these antibodies lead to NMO symptoms remains unresolved. It is tempting to speculate that anti-AQP4 antibodies are not harmful if they circulate peripherally and as long as they are excluded from the blood brain barrier.…”
Section: Pathogenic Role Of Anti-aqp4 Antibodies and T Cells In Nmomentioning
confidence: 99%
“…It can especially help early the introduction of therapy in NMO spectrum diseases (Figs 1 and 2), and might have a prognostic value in NMO; seropositivity has been suggested to be associated with more frequent relapses, greater attack-related disability, higher probability of brain lesions and more extensive lesions on spinal cord MRI. 6,31,58,60,100,[106][107][108][109] However, the lack of such associations has also been reported. 4,26,61,110 Anti-AQP4 antibody-positive Japanese patients with optico-spinal MS (OSMS) might be immunologically different from antibody-negative OSMS patients.…”
Section: Brain Mrimentioning
confidence: 99%
“…[28][29][30] However, myelin-specific T cell-mediated inflammation was necessary for pathogenecity. Lesions predominated in brain areas targeted by such autoreactive T cells and expressed high levels of AQP4; [28][29][30] (vii) anti-AQP4 antibodies can be present in the sera years before the first clinical event; 31 and (viii) removing circulating antibodies by plasma exchange in patients with NMO is beneficial. 32 Considering all these data, the generation of anti-AQP4 antibodies and their presence in the systemic circulation might initiate the disease (i) on disruption of the blood-brain barrier and (ii) under inflammatory conditions of the CNS.…”
Section: Introductionmentioning
confidence: 99%